ANALISIS PERGESERAN BAHASA BAKU MENJADI BAHASA GAUL DALAM KOMUNIKASI MAHASISWA - Chintya Bella Hutabarat; Elvi Silvi Yanti Pulungan; Jenni Romauli Tamba; Selvia Priska Pasaribu; Nurul Azizah (STKIP Subang, 2026)
This study aims to determine how students at Medan State University use everyday language. Do they prefer formal or slang? It also aims to determine what makes them choose to use slang. To conduct this study, we used a survey method by distributing questionnaires to 30 students from various departments. We randomly selected them. Our questionnaire consisted of 19 questions covering information about themselves, their communication habits, their use of slang, and their thoughts on formal language. The results showed that the majority of students, 96.7%, use slang in their daily lives. The main reason they use slang is because they feel more comfortable and relaxed communicating with it. WhatsApp is the communication platform most used by students, with around 90%. The most popular slang words among them are mager (feeling tired), gabut (feeling tired), healing (healing), baper (feeling tired), and bucin (feeling). However, interestingly, around 53.3% of students admitted to having used slang unconsciously in formal situations. This indicates that slang is beginning to creep into situations that should be more formal. The majority of students, 56.7%, believe that using slang does not significantly impact their ability to use formal language. However, 46.7% agree that slang can threaten the sustainability of the Indonesian language. Therefore, more serious language development efforts on campus are needed to ensure students can use appropriate language in appropriate situations.